Ali Manshur PENDAMPINGAN PENGAJIAN KHOTMILQUR’AN JUM’AT LEGI DI MUSALA MIFTAHUL JANNAH DESA KEDUNGRINGIN : PENDAMPINGAN PENGAJIAN KHOTMILQUR’AN JUM’AT LEGI DI MUSALA MIFTAHUL JANNAH DESA KEDUNGRINGIN - Ali Manshur Ali Manshur; Ayu Apriliani; Sri Wahyuni; Ahmad Nur Fuadi (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2025)
This mentoring aims to describe the assistance of Khotmil Qur'an recitation on Friday Legi at Miftahul Jannah mosque in Kedungringin village. Using the Participation Activity Research (PAR) approach through assistance, namely (1) Initial Mapping (2) paying attention to people's ideas (3) Uniting with the people (4) Translating ideas into action (5) Repeating repeatedly. The subjects of this service consisted of Jama'ah Musala Miftahul Jannah. Data collection techniques are interviews, observation and documentation. The results of the mentoring showed that the Khotmil Qur'an recitation activities on Friday had a positive impact on the community in the Miftahul Jannah Musala environment. Among them, the religious atmosphere is more pronounced, life is more harmonious, and the Musala also has financial cash.